P564 Validation of the IBD-Disk instrument in a Portuguese cohort. (27th May 2021) - Silva Mendes, S; Ferreira, P; Antunes, P; Gonçalves, M; Leal, T; Gonçalves, B; Rebelo, A; Arroja, B; Caetano, A C; Gonçalves, R; Soares, J B
Abstract: Background: Inflammatory bowel disease (IBD) affects several dimensions of health-related quality of life. The IBD-Disk scale was designed to provide immediate illustration of disability reported by patients with IBD, previously validated in two cohort studies. The aim of this study is to validate the IBD-Disk in a Portuguese cohort in a clinical setting according to the COnsensus-based Standards for the selection of the health Measurement INstruments (COSMIN) recommendations. Methods: After translation to Portuguese, a group of IBD patients was invited to fill-in the IBD-Disk at baseline (T0), after 2 weeks (T1), and after 3 months (T2), from July 2020 to February 2021. At T0 and T2 the patients also completed the IBD-Disability Index. We evaluated reliability (internal consistency, test-retest, and inter-rater reliability and measurement error), construct validity, responsiveness, and interpretability. Results: At baseline, 154 patients (107 - Crohn′s disease; 46 - ulcerative colitis) completed the IBD-Disk. After 2 weeks and 3 months, 64 and 114 patients repeated the questionnaire, respectively. Factor analysis confirmed the unidimensionality of the scale and reduced the final version to 10 items. Internal consistency was excellent with a Cronbach's α of 0.916. The intraclass correlation coefficient was 0.95 for test-retest (baseline and 2 weeks). To evaluate construct validity, the IBD-Disk was compared with the IBD-Disability Index with a significative positive correlation (r=0.850; p<0.001). IBD-Disk scores ranged from 0 to 93 with a mean of 38.18±25.39. Female gender (β =0, 3; p<0, 001) and professional inactivity (β=0.28, p=0.014) were associated with higher IBD-Disk scores. Neither floor nor ceiling effects were observed. Conclusion: The Portuguese version of IBD-Disk is a reliable, valid, and responsive tool to assess disability in Portuguese IBD patients. This study confirms the utility of this instrument in the evaluation of IBD patients in diverse populations.